Relative sparing of dopaminergic terminals in the caudate nucleus is a feature of rest tremor in Parkinson’s disease - Marcelo D. Mendonça; Pedro C. Ferreira; Francisco Oliveira; Raquel Barbosa; Bruna Meira; Durval C. Costa; Albino J. Oliveira-Maia; Joaquim Alves da Silva (npj Parkinson's Disease)
Abstract Resting tremor (RT) is a Parkinson’s disease (PD) symptom with an unclear relationship to the dopaminergic system. We analysed data from 432 subjects from the Parkinson’s Progression Markers Initiative, 57 additional PD patients and controls and 86 subjects referred for dopamine transporter single-photon emission computed tomography (DaT-SPECT). Caudate binding ratio (CBR), but not putamen binding ratio, was higher in RT patients. Furthermore, higher baseline CBR was linked to RT development. In the smaller cohorts, a 4–6 Hz oscillation-based metric from inertial sensors correlated with RT amplitude, distinguished controls from patients with reduced DaT binding and correlated with CBR in the latter group. In silico modelling uncovered that higher CBR in RT patients explained correlations between RT and DaT-SPECT found in several datasets, supporting a spurious origin for ipsilateral correlations between CBR and RT. These results suggest that caudate dopaminergic terminals integrity is a feature of RT with potential pathophysiological implications.